The value of internal jugular vein collapsibility index in sepsis - KARARMAZ, ALPER; BİLGİLİ, BELİZ; CİNEL, İSMAİL HAKKI (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2016)
BACKGROUND: Rapid, accurate, and reproducible assessment of intravascular volume status is crucial in order to predict the efficacy of volume expansion in septic patients. The aim of this study was to verify the feasibility and usefulness of the internal jugular vein collapsibility index (IJV-CI) as an adjunct to the inferior vena cava collapsibility index (IVC-CI) to predict fluid responsiveness in spontaneously-breathing patients with sepsis. METHODS: Three stages of sonographic scanning were performed. Hemodynamic data were collected using the Ultrasonic Cardiac Output Monitor IA system (Uscom, Ltd., Sydney, NSW, Australia) coupled with paired assessments of IVC-CI and IJV-CI at baseline, after passive leg raise (PLR), and again in semi-recumbent position. Fluid responsiveness was assessed according to changes in the cardiac index (CI) induced by PLR. Patients were retrospectively divided into 2 groups: fluid responder if an increase in CI (Delta CI) >= I5% was obtained after PLR maneuver, and non-responder if Delta CI was <15%. RESULTS: Total of 132 paired scans of IJV and IVC were completed in 44 patients who presented with sepsis and who were not receiving mechanical ventilation (mean age: 54.6 +/- 16.1 years). Of these, 23 (52.2%) were considered to be responders. Responders had higher UV-CI and IVC-CI before PLR maneuver than non-responders (p<0.001). IN-CI of more than 36% before PLR maneuver had 78% sensitivity and 85% specificity to predict responder. Furthermore, less time was needed to measure venous diameters for IN-CI (30 seconds) compared with IVC-CI (77.5 seconds; p<0.001). CONCLUSION: UV-CI is a precise, easily acquired, non-invasive parameter of fluid responsiveness in patients with sepsis who are not mechanically ventilated, and it appears to be a reasonable adjunct to IVC-Cl.
Keywords: Collapsibility index; fluid therapy; inferior vena cava; internal jugular vein; INFERIOR VENA-CAVA; PREDICTING FLUID RESPONSIVENESS; CENTRAL VENOUS-PRESSURE; RESPIRATORY CHANGES; VOLUME STATUS; SEPTIC SHOCK; ULTRASOUND; DIAMETER; GUIDE